ISOLATION, IDENTIFICATION AND SENSITIVITY OF AMILOLITIC BACTERIA FROM MANGROVE ECOSYSTEM SEDIMENT IN PURNAMA MARINE STATION DUMAI ON THE PATHOGENIC BACTERIA - Silitonga, Lamtiur Rotua; Nursyirwani, Nursyirwani; Effendi, Irwan (Asian Journal of Aquatic Sciences, 2019)
Litter from the weathering of dead mangrove stems and leaves contains a lot of starch which has potential to be degraded by amylolytic bacteria into simple compounds with the help of the amylase enzyme. Amylolytic bacteria are bacteria that hydrolyze starch into simpler compounds namely glucose with the help of the amylase enzyme. This study aims to 1) isolate, identify and test sensitivity of amylolytic bacterial isolates found at the Purnama Dumai Marine Station, 2) the ability of amylolytic bacterial isolates to inhibit the growth of pathogenic bacteria (Escherichia coli, Pseudomonas aeruginosa and Vibrio alginolyticus) and 3) to determine the of amylolytic bacterial species by 16S rRNA sequence analysis. The results showed 10 bacterial isolates (TR 2, TR 6, TR 7, TR 9, TR 11, TR 13, TR 15, TR 16, TR 18 and TR 20) were able to inhibit the growth of pathogenic bacteria (E.coli, P.aeruginosa and V.alginolyticus). The sensitivity test of isolate TR 20 against E.coli was categorized into weak with inhibition zone diameter of 4.65 mm. Sensitivity of isolate TR 6 against P.aeruginosa was categorized into medium with inhibition zone diameter of 5.22 mm. Then sensitivity of isolate TR 11 against V.algynolyticus was categorized into medium with inhibition zone diameter of 5.55 mm. DNA analysis using 16S rRNA method and BLAST analysis showed similarity of each isolate. Isolate TR 6 was similar to Bacillus paramycoides strain MCCC 1A04098, isolate TR 11 was in a group of Enterobacter cloacae strain ATCC 13047 and TR 20 was in a group of Vibrio harveyi strains of NBRC 15634